Pentostatin/Cyclophosphamide with or without Rituximab: an effective regimen for patients with Waldenström's macroglobulinemia/lymphoplasmacytic lymphoma - Hensel, Manfred; Villalobos Bollen, Matthias Americo; Kornacker, Martin; Krasniqi, Fatime; Ho, Anthony Dick (Clinical lymphoma & myeloma, 2005)
Background - Pentostatin has demonstrated significant activity as a single agent in patients with low-grade B-cell and T-cell lymphomas and is less myelosuppressive than other purine analogues. - Patients and Methods - We conducted a phase II trial with the combination regimen of PC-R (pentostatin/cyclophosphamide with or without rituximab) in 14 patients with Waldenström's macroglobulinemia (WM) and 3 patients with lymphoplasmacytic lymphoma (LL) without monoclonal serum immunoglobulin M (IgM), followed by a maintenance regimen with rituximab (375 mg/m2 every 3 months) for patients exhibiting a complete response (CR) or a partial response (PR) after 4-6 cycles. Nine patients were untreated, and 8 had been previously treated with 1-3 regimens. The first 9 patients received PC therapy (pentostatin 4 mg/m2 plus cyclophosphamide 600 mg/m2), and 8 patients received the same combination with rituximab 375 mg/m2 on day 1. Cycles were repeated every 3 weeks. - Results - An objective tumor response after PC and PC-R was confirmed in 11 of 17 evaluable patients (64.7%), with 2 CRs (11.7%) and 9 PRs (52.9%). In patients who received rituximab (n = 13) simultaneously or subsequently, the overall response rate was 76.9%. Grade 2/3 nausea and grade 2 vomiting was generally mild based on World Health Organization criteria. Grade 3 hematologic toxicity occurred after 9 of 49 cycles (18.3%), and grade 4 toxicity occurred after 2 cycles (4%). Ten patients were subsequently treated with rituximab every 3 months for 2-9 cycles to date (median, 4 cycles). No patients have had disease relapse to date, and all exhibited stable IgM serum levels. In 3 patients with a PR after completion of chemotherapy, remission has improved further, with normalization of the IgM level in 1 patient and another patient exhibiting a CR. - Conclusion - Our data indicate that PC-R is safe and highly effective in patients with WM. Maintenance therapy with rituximab for WM as a single infusion every 3 months can be administered safely and can improve remission status.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 03.12.2021